The Needs of the Many Do Not Outweigh the Needs of the Few: The Limits of Individual Sacrifice across Diverse Cultures - Sheskin, Mark (2018)
A long tradition of research in WEIRD (Western, Educated, Industrialized, Rich, Democratic) countries has investigated how people weigh individual welfare versus group welfare in their moral judgments. Relatively less research has investigated the generalizability of results across non-WEIRD populations. In the current study, we ask participants across nine diverse cultures (Bali, Costa Rica, France, Guatemala, Japan, Madagascar, Mongolia, Serbia, and the USA) to make a series of moral judgments regarding both third-party sacrifice for group welfare and first-person sacrifice for group welfare. In addition to finding some amount of cross-cultural variation on most of our questions, we also find two cross-culturally consistent judgments: (1) when individuals are in equivalent situations, overall welfare should be maximized, and (2) harm to individuals should be taken into account, and some types of individual harm can trump overall group welfare. We end by discussing the specific pattern of variable and consistent features in the context of evolutionary theories of the evolution of morality.